Friendships and social acceptance of children with disabilities: the role of classroom quality, individual skills, and ECEC dosage - Ferreira, M. (2019)
Positive social experiences with peers are important for children with disabilities attending inclusive early childhood education (ECE). This study investigated the associations between classroom quality; children’s verbal, social, and Behavioral skills; and the friendships and social acceptance of children with disabilities, while testing the moderating effects of ECE dosage. Eighty-six children with disabilities (63 boys; Mage = 67.53 years, SD = 10.54 years), attending 86 inclusive ECE classrooms from the Metropolitan Area of Lisbon, Portugal, participated in the study. We found no effects of classroom quality on children’s social acceptance and friendships and ECE dosage did not moderate this association. However, ECE dosage moderated the association between children’s individual skills and their social acceptance and friendships. Findings suggest that more time in ECE is not enough to support children’s social acceptance, particularly for children with increased language and behavioral difficulties, who likely require more intensive and individualized interventions to support their peer-related social experiences.